Prostatosymphyseal fistula and osteomyelitis pubis following transurethral resection of the prostate: CT and MRI findings. Issue 6 (23rd April 2015) - Plateau, Benjamin; Ruivard, Marc; Montoriol, Pierre‐François
Summary: We present a very rare case of osteomyelitis pubis in a 75‐year‐old male patient due to a prostatosymphyseal fistula, which constituted a few weeks after trans‐urethral resection of the prostate. The patient had a previous history of prostatic carcinoma treated by radiotherapy, which may have played a role in the development of the fistula. Computed tomography with excretory phase and magnetic resonance imaging were performed and enabled to make the final diagnosis.